Tangible Digital Play in Australian and U.S. Preschools. (3rd April 2019) - Berson, Ilene R.; Murcia, Karen; Berson, Michael J.; Damjanovic, Victoria; McSporran, Virginia
Abstract: Drawing on data from preschools in Australia and the United States, the authors highlight strategies to help teachers demystify the process of engaging young learners with tangible technologies and showcase how robotic manipulatives serve as catalysts for peer collaboration, socio–emotional development, and creative problem solving.